The Effect of Coffee Bean Particle Size and Citric Acid Concentration on the Caffeine Content of Arabica Ground Coffee - Kalaswari, Sita; Yulistiani, Ratna; Jariyah, Jariyah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Arabica coffee is a coffee commodity that is widely found in Indonesia because it is considered superior in terms of taste. Arabica coffee contains various biochemical compounds, one of which is caffeine, which is known to overcome drowsiness and reduce physical fatigue. However, caffeine use can also lead to negative side effects, such as anxiety, increased blood pressure, and decreased fine motor skills. This study addresses the public demand for lower caffeine coffee to minimize these side effects. The research focuses on reducing caffeine levels by examining coffee bean size and solvent concentration during decaffeination. . The method used was a completely randomized design (CRD) factorial pattern with two factors and two replications. The first factor was coffee bean particle size (4 mesh, 6 mesh, and 8 mesh) and the second factor was maceration process with citric acid solution concentration (1%, 3%, and 5%). Data were analyzed using Analysis of Varience (ANOVA) and Duncan's Multiple Range Test (DMRT) at the 5% level. The results showed that the treatment of 8 mesh coffee bean size with 5% citric acid solution concentration produced the best caffeine content (1.324 mg/g). In addition, the characteristic values of moisture content (3.436%), ash content (2.065%), and phenol content (29.472 mg GAE/g), were obtained. And organoleptic test results with attributes of fragrant-very fragrant aroma (3.55), blackish-brown-black color (3.65), and bitter-very bitter taste (3.5).